OPTIMIZING EDUCATIONAL EXCELLENCE: THE DYNAMIC IMPACT OF TRANSFORMATIVE LEADERSHIP ON TEACHER AND STUDENT PERFORMANCETHROUGH INNOVATION AND COLLABORATION - Ignatius Septo Pramesworo; Loso Judijanto; Yance Manoppo; Elvi Rahmi; M. Yemmardotillah (Adisam Publisher, 2023)
In pursuing educational excellence, this study delved into the dynamic impact of transformative leadership on teacher and student performance, emphasizing innovation and collaboration. Employing a comprehensive mixed-methods research design, the research explored the multifaceted dimensions of transformative leadership in the educational context. Data collection involved surveys to quantify perceptions and in-depth interviews to capture nuanced insights, ensuring a holistic understanding of leadership dynamics. The findings revealed that transformative leadership significantly influenced teachers, fostering heightened dedication and professional growth. Students, in turn, experienced a more enriching learning environment, leading to improved academic outcomes and socio-emotional well-being. The study also identified collaborative decision-making and supportive school culture as pivotal within the transformative leadership paradigm.